GASTROINTESTINAL HABITS ANALYSIS IN CHILDREN WITH AUTISM SPECTRUM DISORDER ASSISTED IN ANÁPOLIS, GOIÁS (CIPEEX, 2025)
Autism or Autism Spectrum Disorder (ASD) is characterized by impairments in motor and psychoneurological development, resulting in qualitative deficits in cognition, communication, and social interaction. Among the manifestations observed in autistic children, gastrointestinal dysfunctions are prominent, compromising the absorption of nutrients essential for growth and development. This study aims to characterize the intestinal habits of children with ASD assisted by the Association of Parents and Friends of Exceptional Children (APAE) in Anápolis, correlating them with anthropometric growth data. A cross-sectional, quantitative, descriptive, and observational study was conducted, involving children attending APAE in Anápolis. Data were collected using the “Assessment Scale of Eating Behavior and Intestinal Alterations in ASD Patients” questionnaire. Anthropometric data were obtained, and descriptive statistics were performed. It was found that children with ASD frequently present gastrointestinal issues, with constipation being the most common symptom. Although most children were within physiological anthropometric parameters for their age, approximately 25% were classified as short or very short, and 21.7% had elevated weight for their age. Gastrointestinal habits in children with ASD may therefore trigger clinical manifestations with potential impact on the quality of life of children and their families. Additionally, there is a higher tendency toward overweight and obesity in children aged 0–5 years.
Keywords: Growth; Gastrointestinal Disease; Autism Spectrum Disorder